Lignocellulose degradation by Phanerochaete chrysosporium: gene families and gene expression for a complex process - Broda, P; Birch, P R; Brooks, P R; Sims, P F (Molecular microbiology, 1996)
Phanerochaete chrysosporium completely degrades lignocellulose. The most recalcitrant component, lignin, is oxidized by the radical products of lignin and manganese peroxidases, whereas cellulose and hemicellulose are hydrolysed. Both peroxidases and cellulases exist as complex families at both the DNA and protein levels. The lignin peroxidases may function principally when mycelium-bound and, therefore, undetectable in culture supernatants. Moreover, methods for the study of P. chrysosporium must be applicable to solid substrate as well as liquid-culture conditions. For these reasons, detailed studies of gene expression, made possible by the reverse transcriptase-polymerase chain reaction method, are essential. Such studies reveal that gene families are subject to differential expression. The cellulase system has some differences from that of Trichoderma reesei; the distinction made between the activities of exocellobiohydrolases and endoglucanases needs to be re-appraised in both species. Current studies also seek to reconstruct the systems of degradation of lignocellulose and its individual components by heterologous expression of individual proteins in recombinant systems, and their use in mechanistic studies singly and in combinations.